2015
DOI: 10.18632/oncotarget.3327
|View full text |Cite
|
Sign up to set email alerts
|

Metformin potentiates rapamycin and cisplatin in gastric cancer in mice

Abstract: Here we showed that pAMPKα and PTEN were down-regulated and p-mTOR, p-S6, p-4EBP1, MMP7, and DCN1 were up-regulated in human gastric cancer tissue samples as compared to that in the noncancerous tissues. Metformin inhibited tumor growth in mice. Also it enhanced cisplatin- or rapamycin-induced reduction of tumor growth as compared with treatment of either drug alone. In addition to activation of AMPK and suppression of the mTOR pathway, a series of increased and decreased genes expression were induced by metfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 43 publications
9
53
0
Order By: Relevance
“…While the mechanisms of action of metformin that confer anticancer and chemopreventive properties are not entirely elucidated; one proposed action is serving as indirect inhibitor of mTOR via AMPK activation. Studies have shown that metformin may mediate some of the anticancer properties via mTOR inhibition in mice and human liver cancer cell lines [21-23]. It has been suggested that mTOR inhibition by AMPK activators may lead to cancer metabolic reprogramming, which is the hallmark of cancer [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…While the mechanisms of action of metformin that confer anticancer and chemopreventive properties are not entirely elucidated; one proposed action is serving as indirect inhibitor of mTOR via AMPK activation. Studies have shown that metformin may mediate some of the anticancer properties via mTOR inhibition in mice and human liver cancer cell lines [21-23]. It has been suggested that mTOR inhibition by AMPK activators may lead to cancer metabolic reprogramming, which is the hallmark of cancer [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Following the first demonstration that breast CSCs, isolated from established cell lines as a CD44 high /CD24 low subpopulation, are sensitive to metformin, which conversely was ineffective in differentiated tumor cells [111], several subsequent papers reported the selective antitumor activity of metformin on CSCs isolated from different cancers [112][113][114][115]. Noteworthy, metformin showed synergic effects in combination with standard cytotoxic drugs affecting tumor development [95,[116][117][118]. Understanding why CSCs exhibit higher sensitivity to metformin is the subject of intensive investigation.…”
Section: Metforminmentioning
confidence: 99%
“…Metformin may indirectly reduce the circulating insulin levels by increasing the sensitivity of peripheral tissues to insulin, thereby impairing the insulin or IGF pathways (42). Phosphatase and tensin homolog deleted on chromosome ten (PTEN) functions as a cancer suppressor by negatively regulating Akt via interruption of the upstream signal from PI3K, and metformin may exert its effect by increasing the level of PTEN and inhibiting mTORC1 expression (43). Metformin directly activates adenosine monophosphate-activated protein kinase (AMPK), which induces the suppression of mTORC1 expression, ultimately decreasing cell growth and proliferation (44).…”
Section: Selection Comparability Outcome ----------------------------mentioning
confidence: 99%
“…In addition, these authors reported that different treatment periods and metformin concentrations may lead to differential miRNA expression, which suggests that the duration and dose of metformin should be considered on an individual basis. Yu et al (43) showed that metformin inhibited cell proliferation and tumor growth by targeting certain essential genes that affect tumor growth, proliferation and metastasis. The authors suggested that the dosage of metformin should be kept low, and that treatment should be continuous.…”
Section: Selection Comparability Outcome ----------------------------mentioning
confidence: 99%